Maternal social determinants of stunting events in Kulon Progo, Yogyakarta - Ayu, Suci Musvita; Sofiana, Liena; Wardani, Yuniar; Haryanto, Yus (Public Health and Preventive Medicine Archive, 2021)
Background and purpose: Kulon Progo District is one of the 100 priority districts in Indonesia for stunting program with a prevalence of 22.65%. The purpose of this research is to identify association between mother’s education, family income and exclusive breastfeeding history with stunting events in Kulon Progo District, Yogyakarta. Methods: This research used a cross sectional design which conducted in Kulon Progo District, Yogyakarta. There were 729 children aged 0-59 months recorded in the integrated service post (posyandu) who met the inclusion criteria. Data collection was conducted using a questionnaire for children and mothers’ characteristics, while stunting status was retrieved from the growth monitoring card. Data analysis was conducted using Chi-Square test. Results: Children in the survey were 53.77% boys and around a quarter (24.69%) were at 25-36 months old. The majority of the mothers (72.98%) were between the ages of 26 and 35 years with high school education (67.35%) and most of them did not work (82.17%). Children with lower maternal education are less likely to experience stunting (PR=0.751; 95%CI: 0.593-0.952; p=0.013), and those from lower income family have almost five fold increased chance of stunting (PR=4.562; 95%CI: 2.643–7.874; p<0.001). Whilst for history of exclusive breastfeeding, the association was not statistically significant with stunting (PR=0.795; 95%CI: 0.529–1.196; p=0.239) Conclusion:There is a relationship between maternal and family education with the probability of stunting, while there is 20% reduced chance of stunting if children were breast fed although it was not statistically significant. Improving maternal awareness on stunting is essential for stunting management programs.